2D ELASTICITY ANALYSIS WITH BOUNDARY ELEMENT METHOD - Supriyono, Supriyono (Universitas Muhammadiyah Surakarta, 2008)
In this paper, a boundary element method for 2D elasticity analysis is presented. The formulations are also presented. Numerical integration is applied to solve the boundary integral equation obtained from the formulation. Quadratic isoparametric elements are used to represent the variation of a variable along an element. Several